Kunstkritikkens senmoderne betingelser - Nielsen, Henrik Kaare (Peripeti, 2016)
The article takes its point of departure in an account of the historical characteristics of the public sphere as a discursive space for civic participation and reflection on common concerns of society. With reference to Kant, the specific role and potentials of art and aesthetic experience in this perspective are outlined, and the classical role of art criticism is presented. Subsequently, contemporary obstacles to the realisation of the cultural public potential of art criticism are identified in tendencies toward cultural particularisation, the contextual framing of the competitive state and the market-oriented development of the mass media, and the dominance of neoliberal populism. These challenges, it is argued, should be countered by a revitalisation of the universal perspective of reflection of the cultural public sphere.